The Overlap Between the Child Welfare and Youth Justice Systems in Manitoba, Canada - Marni Brownell (International Journal of Population Data Science, 2018)
Introduction Manitoba has one of the highest rates of children taken into care of child welfare services (Child and Family Services; CFS) in the world, and also one of the highest youth incarceration rates in Canada. Policy-makers recognize there is overlap between these systems; the extent of that overlap is unknown.